2019
DOI: 10.1017/s1092852919001032
|View full text |Cite|
|
Sign up to set email alerts
|

Binge eating disorder revisited: what’s new, what’s different, what’s next

Abstract: Binge eating disorder (BED) is the most common type of eating disorder. According to the most recent data available, the estimated lifetime prevalence of BED among US adults in the general population is 0.85% (men 0.42% and women 1.25%). Among psychiatric treatment populations, prevalence is several-fold higher. Although many people with BED are obese (BMI ≥ 30 kg/m2), roughly half are not. In the DSM-5, BED is defined by recurrent episodes of binge eating (eating in a discrete period of time, an amount of foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 79 publications
0
21
1
12
Order By: Relevance
“…Pharmacological agents that treat BED and reduce impulsivity symptoms, including lisdexamfetamine dimesylate (LDX), may be especially effective in individuals with difficulties related to general impulsivity. 4,69,70 Treatment trials for BED may benefit from investigations of general impulsivity and its effect on treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological agents that treat BED and reduce impulsivity symptoms, including lisdexamfetamine dimesylate (LDX), may be especially effective in individuals with difficulties related to general impulsivity. 4,69,70 Treatment trials for BED may benefit from investigations of general impulsivity and its effect on treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…2 BED is characterized by a recurrent pattern of binge eating (i.e., consuming large quantities of food in a short period of time while experiencing a subjective sense of loss of control) associated with marked distress and without weight-compensatory behaviors. 3,4 One factor thought to contribute to the development and maintenance of binge-eating psychopathology is impulsivity, a multidimensional construct that reflects a propensity to engage in increased reward-seeking behavior and poor reward-related decision-making. 5 Impulsivity differs from compulsivity, 6 although obsessions/compulsions about food are associated with frequency of binge eating and BED severity.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, appetite-regulating substances including leptin, neuropeptide Y, ghrelin, peptide YY, and orexin may contribute to the sex-related differences in the association between BS and BMI, as several human and animal studies have reported the possibility of sex-related differences in these substances [ 28 , 29 , 30 , 31 ]. Consistently, eating disorders such as anorexia nervosa and binge eating disorder have been reported to be more prevalent in women than in men [ 32 , 33 ]. However, it is unknown whether BS in low-body-weight men is attributable to such eating disorders or impaired mental health, although BS may be associated with depressive symptoms and mood disorders [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive-behavioural therapy (CBT), interpersonal therapy (IPT), and dialectical behaviour therapy (DBT) are considered first-line treatments for individuals with BN and BED [25][26][27]. However, meta-analyses and review studies indicate that available conventional treatments have difficulties in decreasing binge eating behaviour, with up to 50% of patients not benefiting from these treatments and remaining symptomatic [27,28]. One reason for this might be that although theoretical models and research concerning binge eating behaviour emphasize impulsivity, the translation of this evidence into treatment is still limited.…”
Section: Introductionmentioning
confidence: 99%